Investigation of the main and interactive effects of mix design factors on the properties of cement emulsified asphalt mortars using Mixture Design of experiment. (10th January 2021) - Delarami, Aref; Mohammadzadeh Moghaddam, Abolfazl; Rasaei Yazadani, Mohammadreza; Najjar, Shima
Highlights: Design of experiment (DOE) and the Mixture Design Method were applied. Mechanical and rheological properties of CA mortars were investigated. Micro-structure of CA mortars was also explored by SEM technique. Experimental results were used to develop models, trace and ternary contour plots. Main and interactive effects of mixture components were inspected. Optimal volumetric mix designs were determined based on the Mixture Design Method. Abstract: This study investigated the effect of mixture components including cement, asphalt emulsion, sand, and water on mechanical and rheological properties of Cement Emulsified Asphalt (CA) mortars (type I and II). For this investigation, compressive strength, elastic modulus, segregation, fluidity (J funnel), and spread diameter and time (specific to type II mortar) tests were performed on fresh and hardened specimens. SEM technique was also employed to inspect the micro-structure of CA mortars. To study the effect of mix design factors and their interactions in the domain where rheological and mechanical requirements are met, the Mixture Design method was used in conjunction with the D-Optimal algorithm to design the experiments and analyze the results. After assuming a quadratic model for the relationships between response variables (mechanical and rheological properties) and independent variables (mixture components) including the main effects and two-way effects, 15 randomized mix designs were obtained for each type of mortar (30 mix designs in total). The test of compressive strength was performed on cubic 50 × 50 × 50 mm specimens at the age of 7 and 28 days. The Elastic modulus of the mortars was determined from the strain-strain diagram pertaining to the 28-day compressive strength specimens. Segregation was evaluated by the use of cylindrical 50 × 50ϕ specimens. Tests of fluidity, spread diameter, and spread time were performed according to the standards of the Ministry of Railways of China. The experimental results were used to develop the estimation models of the responses, and the effect of factors and their interactions on mechanical and rheological properties were studied at 95% confidence level. The estimated statistical models could accurately predict the performance of the mortars and were therefore employed to find the optimum combinations of mixture components. Trace and ternary contour plots were drawn to analyze and discuss the effects of mixture components and their interactions on the behavior of type I and type II mortars in each experiment. Finally, the superposition principle was used to combine the responses collected from the experiments, and a series of optimum mix designs based on low, moderate, and high cement contents were devised for both types of mortar.